On innocent victims and demons in Argentina (1983-1985) - Martin, Lucas Gonzalo (2012)
On 24 March 1976 began the so-called "Process of National Reorganisation" (Proceso de Reorganización Nacional). This dictatorship, the last in Argentina's history, marked a turning point, distinguishing itself from preceding dictatorships by waging terror and carrying out forced disappearances. The Proceso established an organised, covert structure for kidnapping individuals who were considered "subversive", imprisoning them in clandestine prisons, torturing and murdering them. To this day, los desaparecidos (the disappeared) have remained hidden from the rest of the world because those responsible, with support from the state, secretly disposed of the corpses. According to the report by the National Commission on the Disappearance of Persons (CONADEP in Spanish), the number of desaparecidos totaled approximately 9 000 victims.